Relação entre o comprometimento e as atividades de exploration e exploitation de conhecimento no processo de sucessão em empresas familiares - D'Arrigo, Fernanda Pauletto (My University, 2016)
The change of command is a challenge for family businesses looking for of the business longterm survival. The succession process is a period of coexistence between predecessors and successors for knowledge sharing between generations to ensure that, the valuable knowledge about the business remains in the organization, therefore that the change of command does not affect the performance and efficiency of company. Given the importance of knowledge in the succession process of family businesses, we highlight knowledge exploration and exploitation activities, carried out individually, but also in the sharing of knowledge between predecessors and successors. Knowledge strategies can be perceived through the exploitation activities - relates to new uses and combinations of existing knowledge to achieve short-term goals, or by means of exploration activities - the search for new knowledge, unknown and often uncertain. Therefore, knowledge exploration ans exploitation activities may be related to individual characteristics and with the relationship with other family members in the routine of the organization. Thus, it allows considering the motivations and involvement of the individual with the family business may have an impact on how such activities are carried out in the organization. In this regard, previous studies indicate that the commitment bases of the members involved in the succession process, thus defining the commitment as a critical aspect of succession. The objective of this research was to analyze the relationship between the commitment and the activities of exploration and exploitation of knowledge of the individuals involved in the process of succession of family businesses. To reach the aim, was carried out a mixed methods approach with an explanatory sequential strategy, and initially collected to be analyzed quantitative data. From the quantitative findings we preceded to the second phase of research, with a qualitative approach that aimed to in depth the results of the quantitative research. The survey was conducted in FCDL-RS considering family businesses of Rio Grande do Sul – Southern Brazil, involved in succession processes. The final results considered 303 respondents participated in the quantitative step and 10 interviewers in the qualitative step. The main contribution of the study is the knowledge exploration and exploitation activities in the individual and the sharing between predecessors and successors, and beyond the commitment relating to these members. The results indicated that, in regard to the individual dimension of analysis, the respondents perform ambidextrous way, both activities. However, in the knowledge sharing dimension, ambidexterity was not identified. Relating the knowledge exploration and exploitation activities in the individual and sharing level with the commitment, the results identified positive and negative relationships. A positive relationship was perceived between affective commitment regarding to the loyalty dimension and exploitation activities for knowledge sharing and combination. On the other hand, negative relationships between the commitment of continuity and affective - regarding the desire to stay in business - and exploration activities on the share to the creation of new knowledge. The result of research indicates that, when discussing the activities of exploration, exploitation and ambidexterity knowledge of the level of analysis and the search context can influence the results of the study
A troca de comando é um desafio para as empresas familiares que buscam a sobrevivência da empresa em longo prazo. O processo de sucessão é também o período de convivência entre predecessores e sucessores para o compartilhamento de conhecimento a fim de garantir que conhecimentos valiosos sobre o negócio se mantenham na organização, para que assim a troca do comando não afete o desempenho e eficiência da empresa. Dada a relevância do conhecimento no processo de sucessão de empresas familiares, destaca-se atividade de exploração de conhecimento, realizadas individualmente, mas também no compartilhamento de conhecimento entre predecessores e sucessores. A exploração de conhecimento pode acontecer por meio das atividades de exploitation, quando refere-se aos novos usos e combinações do conhecimento existente para atingir as metas de curto prazo, ou por meio das atividades de exploration, quando refere-se à busca por novos conhecimentos, desconhecidos e muitas vezes incertos. Por isso, as atividades de exploração de conhecimento se relacionam às características individuais na relação com demais membros da família, na rotina da organização. Fatores referentes à motivação e ao envolvimento do indivíduo com o negócio familiar podem ter influência em como tais atividades são realizadas na organização. Neste aspecto, estudos apontam as bases do comprometimento dos membros envolvidos no processo de sucessão como um aspecto crítico na sucessão. O objetivo desta pesquisa foi analisar a relação entre o comprometimento e as atividades de exploration e exploitation de conhecimento dos sujeitos envolvidos no processo de sucessão de empresas familiares. A abordagem adotada para a pesquisa foi a de métodos mistos com estratégia sequencial explanatória, sendo que incialmente coletou-se a analisou-se dados quantitativos. A partir dos achados quantitativos procedeu-se a segunda fase da pesquisa, de abordagem qualitativa com o objetivo de aprofundar os resultados da pesquisa quantitativa. A pesquisa foi aplicada na Federação das Câmaras de Dirigentes Lojistas do Rio Grande do Sul (FCDL-RS) considerando empresas familiares do Rio Grande do Sul envolvidas em processos sucessórios. Participaram da etapa quantitativa 303 associados e 10 associados participaram da etapa qualitativa. Os resultados indicaram que no nível individual de análise os respondentes realizam de forma ambidestra, ambas as atividades, exploration e exploitation. Já no nível do compartilhamento de conhecimento entre sucessores e predecessores, a ambidestria não foi identificada. Ao relacionar as atividades de exploration e exploitation de conhecimento individuais e no compartilhamento com o comprometimento, identificou-se relações positivas e negativas. A relação positiva foi percebida entre o comprometimento afetivo na dimensão referente à lealdade dos indivíduos ao negocio da família e as atividades de exploitation no compartilhamento e combinação de conhecimentos. Por outro lado, foram identificadas relações negativas entre o comprometimento de continuidade e afetivo, na dimensão referente ao desejo em permanecer na empresa e as atividades de exploration no compartilhamento para a criação de novos conhecimentos. O resultado da pesquisa indica que, ao discutir as atividades de exploration, exploitation e ambidestria de conhecimento o nível de análise e o contexto da pesquisa podem influenciar nos resultados do estudo.
Keywords: Empresas familiares - Administração; Empresas familiares - Sucessão; Family corporations - Management; Family-owned business enterprises - Succession